Vom Chirurgen zum Verleger – Das Jahrhundertleben des Gottfried Bermann Fischer (1897–1995) - Bruns, Florian (DMW - Deutsche Medizinische Wochenschrift, 2018)
Gottfried Bermann Fischer was a German-Jewish physician and publisher who dedicated his life to the S. Fischer publishing company which ranks among the most significant German-language publishers in the 20th century. In 1925 Bermann left his position as a surgeon and married Brigitte Fischer, daughter of the company’s founder Samuel Fischer. Now called Bermann Fischer he became a passionate publisher and steered the company through the Weimar Republic and Nazi years, publishing authors like Hermann Hesse, Thomas Mann, and Alfred Döblin. Fearing the Nazi terror Bermann-Fischer left Germany in 1936 with his family and parts of the company. From his exile in Austria, Sweden, and later in the United States Bermann Fischer carried on with publishing. In 1950 the S. Fischer publishing company was reestablished in Frankfurt, West Germany. Bermann Fischer and his wife brought out the works of Sigmund Freud and books like Alexander Mitscherlich’s “Doctors of Infamy”. Through these publishing activities Bermann Fischer had a significant impact on public debates about medicine and its past in Germany.
Keywords: Gottfried Bermann Fischer; Exil; Medizin und Literatur; Nationalsozialismus